KONDISI FISIK ATLET PERSATUAN ATLETIK SELURUH INDONESIA KABUPATEN KAYONG UTARA - Ardian Ardian; Andika Triansyah; Mimi Haetami (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2021)
AbstractThis research is based on the absence of an athlete data base on the level of physical condition of PASI athletic athletes in North Kayong Regency. This study intends to find out how big the level of physical condition of PASI athletes in North Kayong Regency. The test results of each component of different physical conditions, the results of each component are converted into T scores and added up. The components of the physical condition studied included the speed of leg muscle strength, arm and shoulder muscle strength, flexibility, and endurance. This type of research is a quantitative descriptive study, with a survey method with test and measurement data collection techniques. The population in this study were 14 athletes, consisting of 10 male athletes and 4 female athletes. This study uses a saturated sampling technique. The results of the research on the physical condition of PASI athletes in North Kayong Regency, which shows the results, for the "good" category there are 7 athletes with a percentage of 50.00%, the "enough" category there are 3 athletes with a percentage of 21.43%, for the "less" category there are 3 athletes with a percentage 21.43% and the "very poor" category has 1 athlete with a percentage of 7.14%. The physical condition of PASI athletes in North Kayong Regency is dominated or in the "good" category with consideration of the frequency of 7 athletes with a percentage of 50.00%. Athletes who are still in the category of less or less need more maximum training so that their physical condition can be even better.Keywords: Physical Conditions; Athlete; Athletics